2020
DOI: 10.1007/s00198-020-05520-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of floor surfaces for injury prevention in care settings: impact forces and horizontal pulling force required to move wheeled equipment

Abstract: Shock-absorbing flooring is one potential solution to prevent fall-related injuries. No standards exist to characterise shock-absorbing healthcare flooring. This study explores two mechanical tests for impact force reduction and horizontal force required to move wheeled objects. An appropriately designed rubber underlay can reduce peak impact by 25% compared to 1% with standard vinyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These findings are consistent with Lachance et al [21], who concluded that while novel compliant flooring materials such as SmartCells and Sorbashock can attenuate the impact force considerably, conventional surfaces cannot notably reduce the exerting force to the hip during a fall. Similarly, Keenan et al [84] concluded that conventional flooring can only provide negligible impact on the force attenuation, and novel flooring materials such as rubber with a honeycomb structure can attenuate the impact force up to 25%. Also, Abdul Yamin et al [26] stated that there is not an obvious difference in terms of trend, magnitude, and maximum GRF resulting from running on different flooring materials, and Simpson et al [25] reported that GRF max ranges from 11.9 to 12.4 kN for four different flooring materials.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with Lachance et al [21], who concluded that while novel compliant flooring materials such as SmartCells and Sorbashock can attenuate the impact force considerably, conventional surfaces cannot notably reduce the exerting force to the hip during a fall. Similarly, Keenan et al [84] concluded that conventional flooring can only provide negligible impact on the force attenuation, and novel flooring materials such as rubber with a honeycomb structure can attenuate the impact force up to 25%. Also, Abdul Yamin et al [26] stated that there is not an obvious difference in terms of trend, magnitude, and maximum GRF resulting from running on different flooring materials, and Simpson et al [25] reported that GRF max ranges from 11.9 to 12.4 kN for four different flooring materials.…”
Section: Discussionmentioning
confidence: 98%
“…[32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48]67,130,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] The high-quality data relating to the ineffectiveness of novel flooring in care homes for reducing injury rates 50 is counterintuitive to laboratory studies, which often indicate the superior shock absorbency in these floors and their comparability to hip protectors in terms of impact absorption. 26,37,136 Without an overlay, the novel underlay used in the care home trial (SmartCells) has been demonstrated to attenuate peak force by up to 33.7%, compared with 2 mm of rigid flooring, in a simulated fall to the hip, 33 and by 80% in a simulated fall to the back of the head. 35 Explanatory factors for the negative findings in this review and their disconnect from the wider laboratory-based research may relate to: l the underlying assumptions of laboratory-based research associated with (1) the biofidelity of test systems, (2) the types of fall-related impacts simulated and (3) the type of impact required to sustain injury (and, conversely, the degree of impact attenuation required to prevent injury) l co-interventions (e.g.…”
Section: Potential Biases In the Review Processmentioning
confidence: 99%
“…On the basis of the results of this study, it was suggested that a structured intervention has the potential to reduce fall incidence and improve quality of life for persons living with a spinal cord injury. Keenan et al (2020) compared floor surfaces for injury prevention in care settings. It was determined that shock-absorbing flooring has the potential to prevent fall-related injuries or decrease the severity of injuries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keenan et al (2020) compared floor surfaces for injury prevention in care settings. It was determined that shock-absorbing flooring has the potential to prevent fall-related injuries or decrease the severity of injuries.…”
Section: Literature Reviewmentioning
confidence: 99%